MANTAIN FOOD SCURITY AND BODY IMUNITY IN THE COVID-19 PANDEMIC - Qoni'ah Nur Wijayani (JCES (Journal of Character Education Society), 2021)
Abstrak: Tujuan kegiatan adalah memberi dukungan kepada masyarakat dalam menanggulangi dan mencegah wabah Covid-19 dengan cara menjaga ketahanan pangan dan imunitas masyarakat melalui sosialisasi serta pelatihan pembuatan dan pengembangan Teknologi Tepat Guna berupa pembuatan table box untuk menanam sayur-sayuran, pembuatan jamu tradisional, pembuatan pestisida dan pembuatan pupuk organik di Desa Tanjungan Kecamatan Driyorejo Kabupaten Gresik. Kegiatan dilakukan dengan metode pembuatan dan pengembangan Teknologi Tepat Guna berupa pembuatan table box, pembuatan pestisida dari bahan alami, pembuatan pupuk organik cair, serta pembuatan minuman herbal yang kemudian disosialisasikan kepada warga Desa Tanjungan dengan memperhatikan standar protokol kesehatan. Sosialisasi dilaksanakan di Kantor Desa Tanjungan selama 2,5 jam dengan jumlah peserta 20 orang. Terlihat warga sangat antusias menanggapi materi yang diberikan karena mayoritas peserta adalah petani yang sangat memahami pengelolaan tanaman dengan baik. Hasil kegiatan ini adalah masyarakat memahami cara pembuatan table box, pembuatan pupuk organik cair, pembuatan pestisida alami dan pembuatan minuman herbal yang bisa diterapkan kepada masyarakat yang notabene adalah para petani.Abstract: The purpose of the activity is to provide support to the community in tackling and preventing the Covid-19 outbreak by maintaining food security and community immunity through socialization and training in the manufacture and development of Appropriate Technology in the form of table boxes for growing vegetables, making traditional herbs, making pesticides and making organic fertilizers in Tanjungan village, Driyorejo subdistrict, Gresik Regency. The activity is carried out by the method of making and developing Appropriate Technology in the form of table box making, the manufacture of pesticides from natural materials, the manufacture of liquid organic fertilizers, as well as the manufacture of herbal beverages which are then disseminated to the residents of Tanjungan Village by paying attention to health protocol standards. Socialization was held at Tanjungan village office for 2.5 hours with the number of participants 20 people. It seems that residents are very enthusiastic to respond to the material given because the majority of participants are farmers who understand crop management well. The result of this activity is the community understands how to make table boxes, the manufacture of liquid organic fertilizers, the manufacture of natural pesticides, and the manufacture of herbal beverages that can be applied to the community that is the farmer.